A multidimensional implicit approach to gender stereotypes - Panerati, Sara; Rubini, Monica; Giannella, Valeria A.; Menegatti, Michela; Moscatelli, Silvia (Frontiers in Psychology, 2023)
Research has widely explained gender inequalities in terms of gender stereotypes, according to which women are considered more nurturing, empathic, and emotional but less competentthan men. Recent evidence highlights that especially women are portrayed along multiple dimensions. In this research, we adopted an implicit Semantic Misattribution procedure to detect whether gender stereotypes have a multidimensional structure and are differently attributed to men and women. Results showed that Competence and Dominance-related terms were considered more masculine ones. In contrast, Morality and Physical Attractiveness were attributed to feminine ideograms to a higher and significant extent than masculine ones. Sociability was related to feminine and masculine ideograms almost to the same extent. The gathered evidence provided a multidimensional picture even composed of more judgement dimensions with reference to women highlighting how it can be difficult for them to meet all those multiple expectancies.